Sequencing Treatment in BRAFV600 Mutant Melanoma: Anti-PD-1 Before and After BRAF Inhibition. Issue 1 (January 2017) - Johnson, Douglas B.; Pectasides, Eirini; Feld, Emily; Ye, Fei; Zhao, Shilin; Johnpulle, Romany; Merritt, Ryan; McDermott, David F.; Puzanov, Igor; Lawrence, Donald; Sosman, Jeffrey A.; Buchbinder, Elizabeth; et al.
Abstract : Novel agents targeting immune checkpoint molecules or mutated BRAF are active therapeutic options for patients with BRAF V600 -mutant melanoma. However, the most effective first-line treatment and the optimal sequencing of these agents have not been well characterized. To explore this, we retrospectively assessed 114 patients from 4 centers with advanced, BRAF V600 -mutant melanoma who received anti-programmed cell death-1 (PD-1)/PD-L1 antibodies. We evaluated clinical outcomes, including objective response rate (ORR), overall survival (OS), and progression-free survival (PFS) to initial and subsequent therapies in patients that received anti-PD-1 first (n=56) versus those that received BRAF±MEK inhibitors (BRAFi) first (n=58). Median OS was similar between these groups (27.5 vs. 40.3 mo, P =0.71). Patients who progressed on anti-PD-1 during the study timeframe had worse outcomes after starting subsequent BRAFi than those who had not received prior anti-PD-1 (median PFS 5 vs. 7.4 mo, median OS 10.6 vs. 40.3 mo). Similarly, patients who previously progressed on BRAFi had seemingly inferior outcomes after starting anti-PD-1 compared with those without prior BRAFi, including ORR (25% vs. 41%), median PFS (2.8 vs. 10.6 mo) and median OS (8.2 vs. 27.6 mo). Notably, patients who benefited >6 months from BRAFi had superior ORR to subsequent anti-PD-1 compared with those with more rapid progression (<6 mo) on BRAFi (34% vs. 15%, P =0.04). We conclude that either BRAFi or anti-PD-1 may be effective regardless of treatment sequence in patients with BRAF V600 -mutant melanoma, but clinical outcomes to front-line therapy are superior. In addition, we suggest a shared "responder phenotype" between BRAFi and anti-PD-1.